2005
DOI: 10.1111/j.1528-1167.2005.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Glia Activation in Developing Rat Hippocampus after Status Epilepticus

Abstract: Summary: Purpose:We investigated the activation of microglia and astrocytes, induction of cytokines, and hippocampal neuronal damage, 4 and 24 h after kainic acid-induced status epilepticus (SE) in postnatal day (PN) 9, 15, and 21 rats.Methods: Limbic seizures were induced by systemic injection of kainic acid. Glia activation and neuronal cell loss were studied by using immunocytochemistry and Western blot. Cytokine expression was analyzed by reverse transcriptasepolymerase chain reaction (RT-PCR) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
110
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 24 publications
14
110
1
1
Order By: Relevance
“…Interestingly, MDMA pretreatment, by itself, was not able to trigger hippocampal astro-or microgliosis. However, 30 mg/kg but not 20 mg/kg KA induced hippocampal injury, astrogliosis and microglial activation, which is generally believed to contribute to neuroinflammation and neurodegeneration (Penkowa et al, 2001;Ravizza et al, 2005). The absence of these glial responses in MDMA group was reasonable, since the recreational regimen applied was not sufficient to produce a great degree of neuronal damage (non Fluoro-Jade B immunoreactive neurons, non-significant loss of serotonergic and dopaminergic terminals) (Colado et al, 2001;O'Callaghan and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MDMA pretreatment, by itself, was not able to trigger hippocampal astro-or microgliosis. However, 30 mg/kg but not 20 mg/kg KA induced hippocampal injury, astrogliosis and microglial activation, which is generally believed to contribute to neuroinflammation and neurodegeneration (Penkowa et al, 2001;Ravizza et al, 2005). The absence of these glial responses in MDMA group was reasonable, since the recreational regimen applied was not sufficient to produce a great degree of neuronal damage (non Fluoro-Jade B immunoreactive neurons, non-significant loss of serotonergic and dopaminergic terminals) (Colado et al, 2001;O'Callaghan and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely,there is also evidence supporting a protective role for innate and adaptive immune cells as they cancontribute to seizure-suppression in animal models of TLE [5,6].Whatever its effect or involvement, a growing body of evidence has supported a role for inflammatory mechanisms in epilepsy. This is mainly supported by the finding of high levels of pro-inflammatory cytokines,such as IL-1β, IL-6 and TNF,inthe cerebrospinal fluid(CSF) or bloodof people with epilepsy, notably TLE [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have revealed that proinflammatory cytokines are involved in the pathophysiology of seizures and may be new targets for therapies against epilepsy (De Simoni et al, 2000;Virta et al, 2002;Turrin and Rivest, 2004;Dubé et al, 2005;Bartfai et al, 2007;Somera-Molina et al, 2007). Because the early postnatal brain also generates cytokines in response to peripheral inflammation and seizures Ravizza et al, 2005), it is likely that the interaction of these cytokines with neuronal elements during development may alter the brain in a manner that makes it more susceptible to seizures as an adult. We therefore tested the hypothesis that postnatal inflammation may make adult animals more vulnerable to a challenge by convulsant drugs via an interaction with cytokines.…”
Section: Introductionmentioning
confidence: 99%